Edukasi Pengelolaan Sampah Organik dan Anorganik di SDN 008 Bukit Bestari - Ridho Theosepty Onedi Purba; Listari Noviyanti; Talitha Nabila; Agung Catur Saputra; Nesha Anggraini Panjaitan; Juleha Juleha; Marini Marini; Benni Saputra; Aurellia Ardhi; Akmal Haadi; Dios Sarkity (BADAN PENERBIT STIEPARI PRESS, 2025)
The issue of waste management remains a serious challenge that requires intervention from an early age. This community service program was carried out at SD Negeri 008 Bukit Bestari, Kelurahan Dompak, involving 100 elementary school students. The method employed was based on the Health Belief Model (HBM) through interactive socialization and the use of a waste decomposition board as an educational medium. The stages of the program included preliminary observation, material delivery, waste sorting practice, and evaluation through a questionnaire. The results showed that students demonstrated high enthusiasm, began adopting environmentally friendly behaviors, and were able to understand the differences between organic and inorganic waste. The installation of educational boards proved effective as a sustainable learning tool, while the practice of utilizing inorganic waste encouraged students’ creativity. In addition, the program created a sense of responsibility for waste management among students. The satisfaction survey revealed that all indicators achieved the “very good” category with an average score above 90%. These findings highlight that an HBM-based approach combined with visual media can enhance environmental awareness among elementary school students and has the potential to foster sustainable behavior. Furthermore, the program's success suggests that integrating waste management education into the school curriculum can be an effective strategy for promoting environmental consciousness and cultivating responsible habits in young learners